Safety and effectiveness of single ProStyle™/ProGlide™ for aortic endovascular procedures: single-style study - Rocco Cangiano; Alessia Di Girolamo; Marta Ascione; Francesca Miceli; Carola D’Amico; Andrea Molinari; Ada Dajci; Antonio Sterpetti; Giovanni Gagliardo; Luca di Marzo; Wassim Mansour (Frontiers in Cardiovascular Medicine)
BackgroundThe Perclose ProStyle™/ProGlide™ Suture-Mediated Closure and Repair (SMCR) System is designed to close the common femoral artery (CFA) access during percutaneous endovascular procedures. Instructions for use (IFU) recommend the use of at least two devices, per single access, and the pre-close technique for arterial sheath sizes greater than 8 F. Besides, recent clinical studies suggest that a single ProStyle™/ProGlide™ pre-implantation can safely close percutaneous access for larger diameters.AimThe purpose of this study was to analyse the efficacy of a single pre-implanted ProStyle™/ProGlide™ in closing the Common Femoral Artery (CFA) access site in patients undergoing aortic endovascular procedures using sheaths with diameter 12–16 French (F).MethodsWe performed a prospective study including 72 consecutive patients who underwent aortic endovascular surgery from December 2022 to June 2024 in our University Hospital. In this group, only a single pre-implanted ProStyle™/ProGlide™ was used to close the access site in the CFA after using sheaths with diameters 12–16 F. The primary endpoint was technical success, defined as the absence of intraoperative open surgical conversion. The secondary endpoint was clinical success, defined as the absence of bleeding, pseudoaneurysms, and arteriovenous fistulas in the peri and postoperative period. We compared the results of this group with a cohort of patients in whom two ProStyle™/ProGlide™ were used to close the access site in the CFA.ResultTechnical success was achieved in all cases (100%). Clinical success was achieved in 98% of cases. Only two minor bleedings occurred: one resulted in a small pseudoaneurysm, completely thrombosed 48 h after the procedure. One patient suffered from CFA dissection, requiring an open surgical endarterectomy. There were no statistically significant differences of clinical and technical success rates between the two groups.ConclusionsThis study demonstrates that a Single ProStyle™/ProGlide™ preimplantation can be safe and effective in the closure of vascular accesses up to 16 Fr, with a low complication rate.